Forêts et changement climatique Comprendre et modéliser le fonctionnement hydrique des arbres - Courbet, François (éditions Quae, 2022)
Among the observed climate changes, the increase in the frequency and intensity of droughts is at the heart of foresters' concerns. The speed and extent of these changes, the long life span of trees, and the impossibility of irrigation are all constraints that make it difficult to meet the challenge of forest adaptation. Although there are many causes, lack of water often plays a central role in the deterioration of tree health. How does a tree function with water? How does it react to drought? What are the means to assess its sensitivity to drought? What is a functioning model and what purpose does it serve? This book answers these questions. To facilitate dialogue between ecophysiological researchers and users of research results, it also presents indicators of the effects of drought on trees and functioning models, with a description of each model developed and used by researchers in France. Above all pedagogical and abundantly illustrated, this summary provides us with all the knowledge we need to understand, observe and anticipate the effects of climate change on forests. It is an indispensable tool for students, teachers, foresters, researchers, development and public policy actors, etc.